Achieving the SDGs: Evaluating indicators to be used to benchmark and monitor progress towards creating healthy and sustainable cities - Giles-Corti, Billie; Lowe, Melanie; Arundel, Jonathan (Health policy (Amsterdam), 2020)
•Given rapid urbanisation, city planning is key to achieving the SDGs.•UN indicator frameworks do not include many determinants of city outcomes.•A more comprehensive set of indicators for cities is required.•This will better facilitate monitoring of progress toward attaining the SDGs. In 2016, the World Health Organization declared that ‘Health is one of the most effective markers of any city’s successful sustainable development’ (World Health Organisation, 2016). With estimates that around 6.7 billion people will live in cities by 2050, 21st century city planning decisions will play a critical role in achieving the United Nations (UN) Sustainable Development Goals (SDGs). They will determine the city structure and access to health-enhancing (or health-damaging) urban environments, and ultimately lifestyle choices that impact both individual and planetary health. Benchmarking, monitoring and evaluating city planning policies and interventions is therefore critical to optimise urban outcomes. In 2017, the UN adopted a global SDG indicator framework, calling for complementary national and regional indicators to be collected by member countries. UN Habitat has also developed an indicator action framework specifically for cities. This paper examined the extent to which the UN indicators will help cities evaluate their efforts to deliver sustainability and health outcomes. It identified inconsistencies between the two UN indicator frameworks. Many of the SDG indicators assess outcomes, rather than the comprehensive and integrated ‘upstream’ policies and interventions required to deliver outcomes on-the-ground. Conversely, the UN Habitat framework incorporates intervention indicators, but excludes health outcome indicators. A more comprehensive approach to benchmarking, monitoring and evaluating policies designed to achieve healthy and sustainable cities and assessing spatial inequities is proposed.